In the past - Elliott, David, 1947- (Somerville, Massachusetts : Candlewick Press, 2018)
Chronically organized by epoch, a poetic introduction to the dinosaur world illuminates a host of creatures both novel and familiar, ranging from the mysterious trilobite to the famed Tyrannosaurus rex.
Publisher's Weekly, February 2018
Kirkus Starred, December 2017
Horn Book, March 2018
3.3
K-3
Keywords: Dinosaurs -- Juvenile poetry; Animals, Fossil -- Juvenile poetry; Children's poetry, American; Dinosaurs -- Poetry; Fossils -- Poetry; Poetry